2014
DOI: 10.1088/1674-1056/23/2/024205
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties and mechanism of Tm3+/Er3+/Yb3+co-doped oxyfluorogermanate glass ceramics containing BaF2nanocrystals

Abstract: Yue-Bo(胡曰博) a) , Qiu Jian-Bei(邱建备) b) † , Zhou Da-Cheng(周大成) b) , Song Zhi-Guo(宋志国) b) , Yang Zheng-Wen(杨正文) b) , Wang Rong-Fei(王荣飞) b) , Jiao Qing(焦 清) b) , and Zhou Da-Li(周大利) c) a) Faculty of Mechanical and Electrical Engineering,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…4, the blue luminescence is stronger than the green and red luminescence. So we think that the intense blue luminescence is not only ascribed to the efficient ET process from Yb 3 þ /Er 3 þ to Tm 3 þ ion [15], but also mostly ascribed to the cooperative UC luminescence of Yb 3 þ ion pairs.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…4, the blue luminescence is stronger than the green and red luminescence. So we think that the intense blue luminescence is not only ascribed to the efficient ET process from Yb 3 þ /Er 3 þ to Tm 3 þ ion [15], but also mostly ascribed to the cooperative UC luminescence of Yb 3 þ ion pairs.…”
Section: Resultsmentioning
confidence: 91%
“…As is well known, one of the efficient ways to obtain the white light is controlling the emission proportion of the three primary colors, i.e., red, green and blue (RGB). There have been some reports on the generation of white light through the control of UC luminescence in three primary colors [14,15]. But the excitation optical power of the UC luminescence in these reports was high, and the specimens had to be fabricated into certain size chip with optically flat surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Germanate glass, especially barium gallo-germanate (BGG) glass, is an important matrix material for mid-infrared fiber lasers because of its superior transparency for infrared light, high solubility of rare-earth ions, high laser damage threshold, excellent chemical and mechanical properties. [1][2][3][4][5][6][7] It has been reported that many pulsed and continuous wave fiber lasers at 2.0 µm could be prepared by using Tm 3+ doped BGG fibers. [8] However, when BGG glass fiber lasers were used in a high-energy ray irradiation environment, such as space applications, high-energy ray would result in darkening appearance of the BGG glass fibers, which is commonly referred to as radiation-induced darkening (RD).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Weakly interacting dopants with rare-earth ions are favourable for the possibility of production of the compact laser. [10][11][12][13] In particular, the case of Er 3+ is of considerable interest, [14][15][16][17][18][19][20][21] since it has been found that the visible and infrared photoluminescence spectra of Er 3+ ions with low concentration in MF 2 -type fluorides are closely related to the different charge compensation centers, mainly resulting from the modification of local site symmetry and local lattice distortion.…”
Section: Introductionmentioning
confidence: 99%